Study of Protein Biomarkers of Diabetes Mellitus Type 2 and Therapy with Vitamin B1 - Samreen Riaz (Journal of Diabetes Research)
In the present research work, the levels of protein biomarkers specific to diabetes mellitus type 2 in the Pakistani population using proteomic technology have been identified and characterized and effect of high dose thiamine has been seen on the levels of these marker proteins. Diabetic patients and normal healthy controls were recruited from the Sheikh Zayed Hospital, Lahore, Pakistan. Total biochemical assays and proteins were estimated by modern proteomic techniques. Some proteins were up- and downregulated in diabetic samples as compared to control and decreased after thiamine therapy, while other protein markers did not show a significant change after the thiamine therapy. The effect of high dose thiamine on the levels of these identified protein biomarkers in the human urine has also been observed. Assessment of the levels of these biomarkers will be helpful in not only early diagnosis but also prognosis of diabetes mellitus type 2.